Assessment of Patients with Intracerebral Hemorrhage or Hemorrhagic Transformation in the VENOST Study - MİDİ, İPEK (KARGER, 2021)
Introduction: Cerebral venous and sinus thrombosis (CVST) may lead to cerebral edema and increased intracranial pressure; besides, ischemic or hemorrhagic lesions may develop. Intracerebral hemorrhages occur in approximately one-third of CVST patients. We assessed and compared the findings of the cerebral hemorrhage (CH) group and the CVST group. Materials and Methods: In the VENOST study, medical records of 1,193 patients with CVST, aged over 18 years, were obtained from 35 national stroke centers. Demographic characteristics, clinical symptoms, signs at the admission, radiological findings, etiologic factors, acute and maintenance treatment, and outcome results were reported. The number of involved sinuses or veins, localizations of thrombus, and lesions on CT and MRI scans were recorded. Results: CH was detected in the brain imaging of 241 (21.1%) patients, as hemorrhagic infarction in 198 patients and intracerebral hemorrhage in 43 patients. Gynecologic causes comprised the largest percentage (41.7%) of etiology and risk factors in the CVST group. In the CH group, headache associated with other neurological symptoms was more frequent. These neurological symptoms were epileptic seizures (46.9%), nausea and/or vomiting (36.5%), altered consciousness (36.5%), and focal neurological deficits (33.6%). mRS was >= 3 in 23.1% of the patients in the CH group. Discussion and Conclusion: CVST, an important cause of stroke in the young, should be monitored closely if the patients have additional symptoms of headache, multiple sinus involvement, and CH. Older age and parenchymal lesion, either hemorrhagic infarction or intracerebral hemorrhage, imply poor outcome.
Keywords: Cerebral venous thrombosis; VENOST; Cerebral hemorrhage